2023
DOI: 10.1177/19458924231176394
|View full text |Cite
|
Sign up to set email alerts
|

Rhinologist Use of Antibiotics With Nasal Packing for Epistaxis

Abstract: Background There is limited evidence supporting the usage of prophylactic antibiotics in the setting of nasal packing for epistaxis. It is unclear what current antiobiotic usage patterns are by otolaryngologists. Objectives Characterize the antibiotic prescribing practices employed by otolaryngologists in the management of epistaxis patients treated with packing as well as the underlying rationale. Explore the impact of experience, geography, and academic affiliation on treatment decisions. Methods An anonymou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this issue, Mallen et al surveyed otolaryngologists to evaluate clinical management patterns and identified antibiotic use most frequently with nondissolvable packing, commonly due to the risk of toxic shock syndrome, and most stop following packing removal. 9…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Mallen et al surveyed otolaryngologists to evaluate clinical management patterns and identified antibiotic use most frequently with nondissolvable packing, commonly due to the risk of toxic shock syndrome, and most stop following packing removal. 9…”
mentioning
confidence: 99%
“…In this issue, Mallen et al surveyed otolaryngologists to evaluate clinical management patterns and identified antibiotic use most frequently with nondissolvable packing, commonly due to the risk of toxic shock syndrome, and most stop following packing removal. 9 From a clinical perspective, meta-analyses are particularly valuable in delivery of evidence-based medical care. In this issue, El-Adem et al systematically reviewed the role of positron emission tomography (PET) scans in evaluation of sinonasal malignancies, to find PET scans are particularly useful for detection of distant metastases, with the exception of sinonasal lymphoma.…”
mentioning
confidence: 99%